Winning Olympic medals matters, but how Canada wins them matters more - Monton, K. (Rutgers University Library, 2026)
For years, high-performance sport in Canada has been shaped by a simple equation: win, or risk losing funding. That pressure has too often produced environments marked by fear, burnout, and silence, with devastating consequences for athlete well-being. Recent reckonings across Canadian sport have made one thing clear: performance at any cost is not just harmful, it`s unsustainable. Yet new research suggests there is another way. In a recently published qualitative case study of Speed Skating Canada, the country`s most decorated Olympic sport, my colleagues and I examined the organizational practices behind its sustained international success. Drawing on interviews and focus groups with athletes, coaches, staff, and leadership, we found a high-performance system that has intentionally aligned excellence with care, and results with respect. This matters, not because Speed Skating Canada is perfect, but because it operates under the same conditions as every other national sport organization: performance-contingent funding, limited resources, and relentless pressure to deliver medals. What distinguishes it is not privilege,but choice